Assessment on drag force distribution of a semi-submersible truss fish cage in currents - Liu, Hang-Fei; Huang, Xiaohua; Pang, Guoliang; Li, Gen; Yuan, Taiping; Hu, Yu; Tao, Qiyou (Frontiers in Marine Science, 2025)
Assessing the current forces exerted on a semi-submersible truss fish cage is crucial for understanding drag force distribution and ensuring the structural safety. The present study employs computational fluid dynamics (CFD) methods and porous media theory to predict the drag forces on a semi-submersible truss fish cage, providing a detailed description of the magnitude and distribution patterns of drag forces on the plane nets, pontoons, columns, and braces. Results indicate that the side plane nets bear the highest forces, contributing 24.3% of the total force. The pontoons and thick columns are the next most affected, contributing 18.7% and 13.8% of the total force, respectively, while the middle cross braces bear the least force at 3.7%. A decrease in current speed leads to reduced drag forces on the downstream side plane nets, columns, pontoons, and braces. However, the projected area of each component in the current direction is a critical factor influencing changes in drag forces. Additionally, the torque generated by the drag forces on the semi-submersible truss fish cage is examined. Center position of the torque can alter the torque direction exerted on the truss net cage, and the transition occurs between 18 cm and 19 cm. The present investigation provides a comprehensive evaluation of the drag force distribution on the semi-submersible truss fish cage, which is significant practical engineering implications.